Economy, Poverty and Ethics in Latin America - Estrella Egas, Manuel (2011)
In this second installment on the subject, the concepts of economics already mentioned in the previous article are analyzed, but this time looked at from the case of Latin America. These three components, taken from the concept of economy, are: the satisfaction of needs, the rational use of non-renewable resources and the study of human behavior, in relation to ethics and their daily actions. The analysis of the Latin American reality, in the light of these three elements, makes it possible to identify that, despite the fact that the living conditions of the region do not present critical situations, in relation to other regions of the world, there is, however, still a high level of inequality and corruption that must be fought.